Potensi Arang Aktif dari Limbah Sabut Pinang (Areca catechu L) Provinsi Jambi sebagai Biosorben - Wiji Utami; Devie Novallyan (Fakultas Pertanian, Universitas Timor, 2019)
The preliminary research was conducted to explore the potency of Areca fiber waste (Areca catechu L) from Tanjung Jabung Timur, Jambi Province as carbon source which would be used as a raw material in biosorben production. Activated carbon production was carried out using physical activation on 400 ͦ C, 300 ͦ C, and without carbonization. The collected activated carbon was sifted using 100 mesh sieve. The biosorbents were characterized by water content, ash content, functional groups, and surface area. Based on the result of this research, it could be concluded that carbonization process can disclose the material pores to increase adsorption. The water content, ash content, and surface area of 300 ͦ C sample were 2 %; 45,72 %, and 25,77 m2g-1, respectively.The functional group on the surface of biosorbent would be interacted with adsorbat in adsorption process.